Transitional Justice for Child Soldiers - Fisher, K. author. aut Link
IX, 228 p.
Keywords: This book examines and offers suggestions for how post-conflict practices should conceptualize and address harms committed by child soldiers for successful social reconstruction in the aftermath of mass atrocity. It defends the use of accountability and considers the agency of youth participants in violent conflict as responsible moral entities.